2006
DOI: 10.1038/sj.bjc.6603173
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, maternal weight and childhood leukaemia

Abstract: There is mounting evidence that childhood leukaemia is associated with high birth weight, but few studies have examined the relationship between leukaemia and other perinatal factors that influence birth weight, such as maternal weight or gestational weight gain. This case-cohort study included 916 acute lymphocytic leukaemia (ALL) and 154 acute myeloid leukaemia (AML) cases diagnosed prior to age 10 years between 1985 and 2001 and born in New York State excluding New York City between 1978 and 2001. Controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 56 publications
5
58
3
2
Order By: Relevance
“…Two neonatal factors that have shown a relatively constant association with an increased childhood cancer risk are high birth weight and neonatal asphyxia. High birth weight as a risk factor has been described repeatedly 7,15,22,23 and was also seen in our material (Table 2) as a birth weight Ն4500 g, or LGA. This has been looked on as an effect of fetal growth factors.…”
Section: Discussionmentioning
confidence: 60%
“…Two neonatal factors that have shown a relatively constant association with an increased childhood cancer risk are high birth weight and neonatal asphyxia. High birth weight as a risk factor has been described repeatedly 7,15,22,23 and was also seen in our material (Table 2) as a birth weight Ն4500 g, or LGA. This has been looked on as an effect of fetal growth factors.…”
Section: Discussionmentioning
confidence: 60%
“…Relative risks for advanced maternal age and childhood leukemia fluctuated around 1.3 in Little's review of >25 studies published before 1998 11 ; several subsequent studies have reported similar findings. 10,16,19,23,44 A small casecontrol study in Mexico examined at maternal age as a risk factor for acute leukemia in children with DS and reported no association. 45 Age was associated with acute leukemia risk as a continuous and categorical variable.…”
Section: Discussionmentioning
confidence: 99%
“…In a population-based cohort, a positive linear relation was reported between birth weight, and childhood ALL and AML (Paltiel et al, 2004;Mclaughlin et al, 2006), more marked in AML among infants (hazard ratio ¼ 8.14, 95% CI: 1.8 -38.9 at age 0 -1 years), being particularly strong among female infants (P ¼ 0.001) (Paltiel et al, 2004). Among the variables included in this study, including maternal origin, socioeconomic status, birth weight of sibling higher than 3500 g and family size, only birth weight retained borderline significance (Paltiel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%